Determinant of FDI Inflows in OIC Countries - Megasari, Tania; Saleh, Samsubar (International Journal of Islamic Economics and Finance (IJIEF), 2021)
This study aims to analyze the determinants of foreign direct investment (FDI) in the Organization of Islamic Cooperation (OIC) country members for the period 2005 to 2018 The determinant variables of FDI are corruption, political stability and macroeconomic variables such as inflation, exchange rates, economic growth, and trade openness. Analysis used in the studyÂ  is the fixed effect model (FEM) of the OIC data panel.The results showed that economic growth and trade openness had a significant influence on foreign direct investment (FDI), while the effects of corruption, political stability, inflation and the exchange rate have no significant effect on foreign direct investment (FDI).